Undecacarbonyl[(4-methylsulfanylphenyl)diphenylphosphane]triruthenium(0): Crystal structure and Hirshfeld surface analysis - Omar Shawkataly,; Hafiz Malik Hussein, Adnelnasir; Siti Syaida Sirat,; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2018)
The title cluster compound, [Ru3(C19H17PS)(CO)11], comprises a triangle of Ru0 atoms, two of which are bonded to four carbonyl ligands. The third metal atom is bound to three carbonyl ligands and the phosphane-P atom of a dissymmetric phosphane ligand, PPh2(C6H4SMe-4); no Ru S interactions are observed. The phosphane occupies an equatorial position and its proximity to an Ru—Ru edge results in the elongation of this bond with respect to the others [2.8933 (2) A ° cf. 2.8575 (2) and 2.8594 (3) A ° ]. In the crystal, phenyl-C—H...O(carbonyl) and carbonyl-O O(carbonyl) [2.817 (2) A ° ] interactions combine to form a supramolecular chain propagating along [111]; the chains pack without directional interactions between them. The carbonyl-O...O(carbonyl) and other weak contacts have an influence upon the Hirshfeld surfaces with O...H contacts making the greatest contribution, i.e. 37.4% cf. 15.8% for O O and 15.6% for H H contacts.